упростите вырожение:

(а - 3)(а - 7) - 2а(3а - 5)

(х - 2)(х + 4) - 2х(1 + х)

2с (Зс + 4) - Зс (2с + 1)

За (2а - 1) - 2а (4 + За)

2

Ответы и объяснения

2013-03-20T11:54:44+04:00

1. a^2-7a-3a+21-6a^2+10a=-7a^2+21

2.x^2+4x-2x-8-2x-2x^2=-x^2-8

3.6c^2+8c-6c^2-3c=5c

4.6a^2-3a-8a-6a^2=-11a

 

 

 

2013-03-20T11:57:15+04:00

(а - 3)(а - 7) - 2а(3а - 5)=a^2-10a+21-6a^2+10a=-5a^2+21

(х - 2)(х + 4) - 2х(1 + х)=x^2+2x-8-2x-2x^2=-x^2-8

2с (Зс + 4) - Зс (2с + 1)=6c^2+8c-6c^2-3c=5c

За (2а - 1) - 2а (4 + За)=6a^2-3a-8a-6a^2=-11a